2020
DOI: 10.32598/jams.23.cov.1889.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Health-promoting Lifestyle and Psychological Well-being on Anxiety Induced by Coronavirus Disease 2019 in Non-medical Students

Abstract: Background and Aim: Anxiety is one of the clinical signs of viral diseases such as Coronavirus Disease 2019 (COVID-19), which can threaten the immune system. This study aims to investigate the effect of health-promoting lifestyle and psychological well-being on COVID-19-induced anxiety in non-medical students Methods & Materials: This is an analytical/correlational study conducted on 307 non-medical students of Islamic Azad University in Tabriz, Iran, who were participated voluntarily in the study. They co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The results indicate no gender-wise differences between germophobia levels different demographic statuses. These findings were also reported by [34][35][36] but are opposed to [37]. Distel et al (2008) examined the genetic and environmental influences in a large sample of Dutch twins on specific phobias.…”
Section: Discussionmentioning
confidence: 80%
“…The results indicate no gender-wise differences between germophobia levels different demographic statuses. These findings were also reported by [34][35][36] but are opposed to [37]. Distel et al (2008) examined the genetic and environmental influences in a large sample of Dutch twins on specific phobias.…”
Section: Discussionmentioning
confidence: 80%
“…Consequently, cardiovascular associations have advised such individuals to rigorously follow health protocols (59). What remains mysterious is the development of heart-related complications in individuals who had never experienced heart conditions prior to contracting COVID-19 (57,60). One of the most perilous complications of this disease is an increased tendency for blood coagulation, elevating the risk of stroke (61).…”
Section: Clinical Characteristics Of Covid-19 Patientsmentioning
confidence: 99%
“…In this regard, several studies have shown that psychological well-being has a significant effect on reducing COVID-19 death anxiety. [ 20 21 ] In addition, other studies have shown that COVID-19 anxiety has a negative effect on mental health. [ 22 23 24 ]…”
Section: Introductionmentioning
confidence: 99%